Star trek: star charts - Mandel, Geoffrey (New York: Pocket Books, 2002)
Este texto contiene los siguientes temas: Alpha quadrant. Beta quadrant. Gamma quadrant. Delta quadrant. Key quadrant
Colección Erwin Buendia Silva 2426
Keywords: Cine - Star Trek